Fluorophore signal detection and imaging enhancement in high refractive index nanowire biosensors - Nicklas Anttu (Nano Express)
Semiconductor nanowires are an efficient platform for fluorescence-based biosensors. Here, we model how a GaP nanowire (i) enhances the excitation intensity at the position of the fluorophore attached to the nanowire sidewall, (ii) enhances the probability to collect photons emitted from the fluorophore, and (iii) through the Purcell effect increases the quantum yield of the fluorophore. With optimized design, we can reach a larger than 10 ^2 enhancement in signal. We also model imaging-based detection. There, waveguiding in the nanowire beats the limitations set by the depth of view in conventional microscopy, enabling the use of a long nanowire to enhance the binding-area for fluorophores. As an example, we can focus to the top of a 4000 nm long nanowire and reach a 25 times sharper image from a fluorophore at the bottom of the nanowire, as compared to such a 4000 nm defocusing in a conventional planar biosensor platform.